Efektivitas Pemberian Esensial Oil Aromaterapi Jahe Merah (Zingiber Officinale Var Rubrum) dalam mengatasi Emesis Gravidarum pada Ibu Hamil - Kusniyanto, Rahayu Eryanti; Triananinsi, Nurhidayat; Hetharia, Christine Irene (POLTEKKES KEMENKES MANADO, 2025)
Background: The incidence of emesis gravidarum in Indonesia, based on observational data, is 24.7% among 2,203 pregnant women. Globally, the incidence is around 14%. Physiologically, the pregnant body adapts to maintain the pregnancy. After fertilization, the body increases the production of hCG hormone to sustain the corpora lutea during the early stages of pregnancy, which also produces estrogen and progesterone. The rise in these hormones affects the body, making it more susceptible to emesis gravidarum. One management approach to reduce the frequency of emesis gravidarum in first-trimester pregnant women is inhalation of Red Ginger Aromatherapy using a diffuser. Ginger contains essential oils, vitamin A, and bitter resin. Its essential oil has a refreshing effect and can block the vomiting reflex. Objective: To determine the effect of Red Ginger (Zingiber Officinale var. rubrum) Essential Oil Aromatherapy on emesis gravidarum in first-trimester pregnant women. Method: This study employed a pre-experimental design with a one-group pretest-posttest approach. The research sample consisted of first-trimester pregnant women experiencing emesis gravidarum who visited the Midwifery Outpatient Clinic at Abepura Regional Public Hospital and met the inclusion criteria. A total of 30 participants were included in one group without a comparison group and were given Red Ginger Aromatherapy using a diffuser. The aromatherapy was administered once daily for 7 consecutive days. The severity of emesis gravidarum was measured before and after the intervention using the PUQE Score. Results: A Paired T-Test showed a statistically significant result with p < 0.001. Conclusion: There is an effect of Red Ginger Aromatherapy on reducing emesis gravidarum in first-trimester pregnant women.